Climate-Smart Agriculture: Do Young People Care? - Manalo, Jaime A.; Saludez, Friedierick M.; Layaoen, Myriam G.; Pagdanganan, Argie M.; Berto, Jayson C.; Frediles, Christina A.; Balmeo, Katherine P.; Villaflor, Jennifer D. (2016)
This paper is about the information-seeking and information-sharing behavior on climate-smart agriculture (CSA) of high school students who participated in the Infomediary Campaign in 2014. This seeks to answer five research questions: (1) What are the indicators that searching and sharing of information by the infomediaries transpired? (2) What are the characteristics of infomediaries who are most likely to share information on CSA? (3) What sort of information can be competently shared by high school students? (4) How is information transferred from the information source (PhilRice) to the farmers? (5) What evidence suggests that information transferred was put to good use by the intended recipients? A survey (N=388) was conducted among eight randomly selected schools, from the pool of 108 schools, nationwide. Focus group discussions, individual interviews, and participant observation were likewise conducted. The Stakeholder Theory and Livelihoods Approach were combined to unpack the findings in this research. Results show that females are more likely to share information than males (p=.071). Land tenurial status (p=.430) and familial background (p=.052) do not seem to influence the information-seeking behavior of young people. Information that is easy to understand and reinforced elsewhere was shared often by students as compared with more complex ones. Several pathways were generated in documenting the infomediation process on CSA with the schools as the nucleus of agricultural information. These are: (1) PhilRice to farmers, (2) PhilRice to teachers to farmers, and (3) PhilRice to teachers to students to farmers.